Effect Concentration of Teak Leaf Extract on the Diameter of the Inhibitory Zone Xanthomonas oryzae - Prasetyo, Hidayat Nur; Pantiwati, Yuni; Chamisijatin, Lise (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Indonesia is an agricultural country with the majority of the population working in the agricultural sector. According to the Central Statistics Agency of Indonesia, rice production in 2022 is estimated at 9.58 million tons, down by 0.04 million tons or 0.41 percent compared to 2021 which was around 9.62 million tons. The rise and fall of rice production was influenced by several problems. One of the causes of the delay in rice production is leaf blight caused by Xanthomonas oryzae pv. oryzae reducing rice yields by 30-40%. This research was to examine the use of teak leaf extract in inhibiting the growth of X. oryzae bacteria. The results showed that there was an effect of various concentrations of teak leaf extract (Tectona grandis) on the inhibition zone of X. oryzae. The effective concentration of teak leaf extract in inhibiting Xanthomonas oryzae bacteria is 20%.